Dysplasia of stomach epithelium at chronic H. pylori-associated gastritis: is everything quite so simple? - T. L. Lapina; A. S. Tertychny; S. S. Pirogov; V. V. Sokolov; I. M. Kartavenko; E. R. Nasretdinova; A. A. Paraskevova; O. A. Storonova; O. S. Lyashenko; Ye. Yu. Yur'yeva; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. Analysis of clinical cases demonstrating differentiated management approach at chronic H. pylori-associated gastritis with stomach epithelium dysplasia.Key points. Detection of high grade (severe) dysplasia is associated to high risk of early, invasive stomach cancer or its rapid development. In presented clinical case adenocarcinoma has been found in 60 year-old male patient with deep submucosa invasion simultaneously with high grade dysplasia. According to comprehensive endoscopic investigation endoscopic treatment option was considered impossible and patient underwent distal subtotal stomach resection with Roux-en-Y anastomosis and D2 regional lymph node dissection. At low grade (mild) dysplasia complex endoscopic investigation is recommended to identify local premalignant lesions of the stomach mucosa, and at ruling them out — to determine adequate therapy. So, in presented clinical case H. pylori eradication therapy in 45-year old patient has led to disappearance of changes suspicious to epithelial dysplasia. The term «indefinite for dysplasia» is applied to atypical changes which can be characterized as of premalignant or reactive nature. It is provisional conclusion which requires specifying endoscopy with guided biopsy and repeated histological conclusion.Conclusion. Prognosis and management approach in the cases with histological conclusion of stomach epithelium dysplasia should be determined according to comprehensive multimodal endoscopic investigation with guided biopsy.